VARIEDADES QUASE EINSTEIN - CARDOSO, Márcia do Socorro Borges de Araújo (2006)
This dissertation is based about two works on quase Einstein manifolds. The first, published in 2000, by M. C. Chaki and R. K. Maity, on quase Einstein manifolds which are not conformally flat, and they determine sufficient condition so that the same ones are conformally flat. Already the second work, published by U. C. De and Gopal Chandre Ghosh, in 2004, establish a relation between the manifolds of amost constant curvature and the quasi Einstein manifolds, find necessary and sufficient conditions for a quasi Einstein manifolds to be of almost constant curvature, in follow prove an existence theorem on quase Einstein manifolds with other such manifolds like weak symmetries and semi-symmetries Ricci.